2004
DOI: 10.1603/0022-0493-97.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Life History of the Bird Cherry-Oat Aphid, <I>Rhopalosiphum padi</I> (Homoptera: Aphididae), on Transgenic and Untransformed Wheat Challenged with <I>Barley yellow dwarf virus</I>

Abstract: The life history of Rhopalosiphum padi (L.) was monitored on transgenic and untransformed (soft white winter wheat plants that were infected with Barley yellow dwarf virus (BLDV), noninfected, or challenged with virus-free aphids under laboratory conditions. Two transgenic soft white winter wheat genotypes (103.1J and 126.02) derived from the parental variety Lambert and expressing the barley yellow dwarf virus coat protein gene, and two untransformed varieties, virus-susceptible Lambert and virus-tolerant Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Cucumber mosaic virus (CMV) induced an increase in plant volatile emissions, and induced Myzus persicae to preferentially feed on the infected plants [34]. Barley yellow dwarf virus (BYDV) can also induce the release of more volatiles from plants and induce prolonged aphid feeding [35]. The behavior of the insect vectors caused virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Cucumber mosaic virus (CMV) induced an increase in plant volatile emissions, and induced Myzus persicae to preferentially feed on the infected plants [34]. Barley yellow dwarf virus (BYDV) can also induce the release of more volatiles from plants and induce prolonged aphid feeding [35]. The behavior of the insect vectors caused virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Viriliferous vectors have reduced fecundities [20,21]. Tomato yellow leaf curl virus (TYLCV) infested vectors Bemisia tabaci (Genadius) also have about for 17-23% shorter longevity and reduced fecundity of about 40-50% [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiment, we used the BYDVinfected wheat plants with increased volatile components (trans-2-hexen-1-al, 2-pentylfuran, phenylacetaldehyde, or decanal) to perform dual-choice bioassays. Trans-2-hexen-1-al and phenylacetaldehyde have been previously reported as herbivore-induced plant volatiles (Cantelo and Jacobson 1979;James 2005). 2-Pentylfuran was previously reported as volatile aroma compounds in rice (Yang et al 2008) and decanal has been reported as a BYDV-induced wheat volatile (Medina-Ortega et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…The vector manipulation hypothesis (VMH) (Ingwell et al 2012) was built upon a framework of plant virus pathosystems (Mauck et al 2012;Luan et al 2014). Specifically, plant viruses can enhance their spread to new host plants by affecting the behavior/performance of mobile vectors which can interact with plant growth stages and disease progression (Jiménez-Martínez et al 2004a, 2004bBelliure et al 2005;Fereres and Moreno 2009). This type of basic research has important theoretical implications for plant virus ecology and evolution as well as applications in integrated pest management because vector-borne plant pathogens are economically important causal agents of serious diseases affecting productivity in agricultural and forestry ecosystems (Eigenbrode and Bosque-Pérez 2016).…”
Section: Introductionmentioning
confidence: 99%